Informal Value Chain Actors' Knowledge and Perceptions about Zoonotic Diseases and Biosecurity in Kenya and the Importance for Food Safety and Public Health - Nyokabi, Simon; Birner, Regina; Bett, Bernard; Isuyi, Linda; Grace, Delia; Güttler, Denise; Lindahl, Johanna (CrossMark, 2017)
Zoonotic diseases, transmitted from animals to humans, are a public health challenge in developing countries. Livestock value chain actors have an important role to play as the first line of defence in safeguarding public health. However, although the livelihood and economic impacts of zoonoses are widely known, adoption of biosecurity measures aimed at preventing zoonoses is low, particularly among actors in informal livestock value chains in low and middleincome countries. The main objective of this study was to investigate knowledge of zoonoses and adoption of biosecurity measures by livestock and milk value chain actors in Bura, Tana River County, in Kenya, where cattle, camels, sheep and goats are the main livestock kept. The study utilised a mixed methods approach, with a questionnaire survey administered to 154 value chain actors. Additional information was elicited through key informant interviews and participatory methods with relevant stakeholders outside the value chain. Our results found low levels of knowledge of zoonoses and low levels of adherence to food safety standards, with only 37% of milk traders knowing about brucellosis, in spite of a sero-prevalence of 9% in the small ruminants tested in this study, and no slaughterhouse worker knew about Q fever. Actors had little formal education (between 0 and 10%) and lacked training in food safety and biosecurity measures. Adoption of biosecurity measures by value chain actors was very low or non-existent, with only 11% of butchers wearing gloves. There was a gendered dimension, evidenced by markedly different participation in value chains and lower adoption rates and knowledge levels among female actors. Finally, cultural and religious practices were shown to play an important role in exposure and transmission of diseases, influencing perceptions and attitudes to risks and adoption of biosecurity measures.
This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http:// creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.
Keywords: Biosecurity measures; Zoonoses; Veterinary public health; Livestock value chains; Disease prevention; Infectious disease; Epidemiology; Disease transmission